Perubahan Output dan Kinerja Sektor Pariwisata di Bali Dalam Masa Pandemi Covid 19 - Muhammad Arif; Silmi Nur Octaviani (Profesional Muda Cendekia Publishing, 2022)
Tourism is one of the sector that greatly affect the country’s income. The tourism sector is the second largest foreign exchange contribution for Indonesia. Bali is one of the provinces that are often visited by local and foreign people. The existence of coronavirus or covid 19 pandemic, makes all matters related to tourism in Bali temporarily stopped. This resulted in the tourism sector experiencing a decline due to covid 19 pandemic. The purpose of this study is to analyze the performance of the tourism sector during the covid 19 pandemic in 2020-2021. This study uses input-output analysis method. The type of data used in this study is secondary data. The results showed that tourism sector during the pandemic experienced turmoil that resulted in a decrease in demand for final output of the economy and Bali’s economic growth is declining during the covid 19 pandemic.